13.8k views
3 votes
PLEASE HURRY Study these equations: f(x) = 2x – 8 g(x) = –5x What is h(x) = f(x)g(x)? h(x) = 10x2 – 40x h(x) = –10x2 + 40x h(x) = –10x + 40 h(x) = 10x – 40

User JerMah
by
6.4k points

2 Answers

2 votes

Answer:

B : h(x) = –10x2 + 40x

Explanation:

this is a late answer but I hope it helps anyone who needs it for the future !!

User Njachowski
by
5.5k points
6 votes

h(x)=
-10x^(2)+40x

Explanation:

given ,
f(x)=2x-8

given,
g(x)=-5x

Given that
h(x)=f(x)g(x)

Let
t_(1) be
k_(1)x^{n_(1)} where
k_(1) \text{ and } n_(1) \text{ are constants}

Let
t_(2) be
k_(2)x^{n_(2)} where
k_(2) \text{ and } n_(2) \text{ are constants}

We know that
t_(1)* t_(2)=k1* x^{n_(1)}* k2* x^{n_(2)}=
k_1k_2x^{n_(1)+n_(2)}

So,
h(x)=(2x-8)(-5x)=
-10x^(2)+40x

User Anuar
by
5.5k points